2018
DOI: 10.5414/cncs109513
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia-induced acute kidney injury in a Caucasian female due to radiographically silent systemic sarcoidosis

Abstract: Abstract. Sarcoidosis is a rare autoimmune disease resulting in formation of non-necrotizing “non-caseating” granulomas generally in the lung. The disease classically strikes African American females in their fourth and fifth decades. The resulting hypercalcemia is a result of 1-α hydroxylase overexpression in granulomas with increased 1,25-dihydroxy vitamin D levels. This phenomenon can also be observed in mycobacterial and fungal infections that produce granulomas in infected patients. Thus, chronic infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The main cause is medication with glucocorticoids. Endogenous overproduction of calcitriol can be accompanied by vitamin D deficiency [40,41]. Kiani et al [42] reported a negative correlation between vitamin D deficiency and pulmonary functional state in patients with sarcoidosis.…”
Section: Calcium and Vitamin D Disturbances In Sarcoidosismentioning
confidence: 99%
“…The main cause is medication with glucocorticoids. Endogenous overproduction of calcitriol can be accompanied by vitamin D deficiency [40,41]. Kiani et al [42] reported a negative correlation between vitamin D deficiency and pulmonary functional state in patients with sarcoidosis.…”
Section: Calcium and Vitamin D Disturbances In Sarcoidosismentioning
confidence: 99%
“…The high serum 1,25-dihydroxyvitamin D levels, hypercalcemia-related renal impairment and recent onset are entirely consistent with published case reports on sarcoidosis. 13,14 The only difference was that, in those cases, serum 25-hydroxyvitamin D levels were normal. The high 1,25-dihydroxyvitamin D in the case report of Auguste and colleagues 1 is not a sign of vitamin D toxicity and is likely a consequence of sarcoidosis.…”
mentioning
confidence: 94%
“…The high 1,25-dihydroxyvitamin D in the case report of Auguste and colleagues 1 is not a sign of vitamin D toxicity and is likely a consequence of sarcoidosis. [13][14][15] The renal biopsy used by Auguste and colleagues does not rule out sarcoidosis. 16 The hydroxychloroquine they used to treat the patient is not a conventional treatment for vitamin D toxicity, but it is a first-line treatment for sarcoidosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Low calcium can lead to circumoral or peripheral paranesthesia, tetany, carpopedal spasm, laryngospasm, and ECG changes from long QT interval to VT arrest [1,2]. While high calcium can cause fatigue, polyuria, polydipsia, nephrolithiasis, peptic ulcer disease, altered mental status, gait instability [3][4][5], myalgia, arthralgia, abdominal pain [4], rare submandibular gland atrophy and sialolithiasis, metastatic pulmonary calcification [6,7], sometimes even inducing acute kidney injury or acute pancreatitis [8][9][10][11][12][13], or being life-threatening [14,15]. The parathyroid gland is an adjacent organ of the thyroid.…”
Section: Introductionmentioning
confidence: 99%